Development of Rural Tourism Area for Equitable Development In Suak Gual Village, Selat Nasik Sub-District, Belitung District - Abdur Rofi; Putu Bagus Gita Mahendra; Aji Purnomo; Tatak Puji Wahyudi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
The potential for nature tourism in Suak Gual Village as a tourist destination in Belitung Regency has not been well managed. This study aims to examine the tourism potential in Suak Gual Village to increase development in disadvantaged areas. Specifically, this study aims to (1) examine the factors inhibiting tourism development in Suak Gual Village, (2) developing the Student Community Service Program for Tourism Development in Suak Gual Village, and (3) evaluating the Student Community Service Program results in Suak Gual Village. This research is action research using qualitative methods. The data collected includes primary and secondary data. Data analysis was using a qualitative descriptive approach. The results showed that the inhibiting factors for the development of Suak Gual Village were low education, accessibility, and infrastructure. The intervention program is classified into three dimensions: (1) the science-technology dimension, (2) the infrastructure dimension, and (3) the agro-marine dimension. The Student Community Service Program has resulted in tourism promotion, the creation of tourism marketing media, assistance for Tourism Awareness Groups, homestay improvements, and registration of homestay bookings on the Traveloka application.